Diversity: Identification of Fish Catched Fisherman of Weru Village, Lamongan District - Rahmat Bayu Fillanthropy; Abdulkadir Rahardjanto; Dwi Setyawan (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Lamongan Regency has great fishery potential, but the results of fishing by fishermen need to be reported to determine its diversity. The purpose of this study was to find out what fish were caught and the diversity of fish caught by fishermen from Weru Villaget. The method of conducting this research was carried out using a descriptive exploratory method with a quantitative approach, with the aim of describing the results of identifying the diversity of fish catches in Weru Village, Lamongan Regency. The results of the research from the catch of fishermen from Weru Village, Lamongan Regency, consisted of 14 fish species. Then the diversity index (H') of station I has a value of H' 0.33; station 2 has H' 0.34; station 3 has a value of H' 0.32; and station 4 has an H' value of 0.34. Then Stations 1, 2, 3, and 4 have an average value of 1.37 so they are classified as low diversity.